Decreased absolute number of peripheral regulatory T cells in patients with idiopathic retroperitoneal fibrosis - Liu, Lu; Yan, Huanhuan; Wang, Yanyan; Xie, Yuhuan; Jiang, Lei; Zhao, Jinfang; Gao, Chong; Li, Xiaofeng; Wang, Caihong (Frontiers in Immunology, 2022)
Objective In order to determine whether the immune balance of T helper 17(Th17)/regulatory T(Treg) is related to the pathogenesis of idiopathic retroperitoneal fibrosis (IRPF), we analyzed the differences in peripheral blood lymphocytes, CD4+T cell subsets and cytokines between patients with IRPF and healthy people to clarify the CD4+T cell subsets, especially Treg cell subsets, and the role of cytokines in the pathogenesis of IRPF. Methods This study included 22 patients with IRPF, 36 patients with IgG4-related diseases (IgG4-RD) without retroperitoneal fibrosis (RPF), and 28 healthy controls. The absolute numbers and percentage of peripheral blood lymphocyte subsets and CD4+T cell subsets in each group were detected by flow cytometry, and the serum cytokine level was detected by flow cytometric bead array (CBA). Results Compared with the healthy group, the absolute value of B cells in peripheral blood of IRPF patients was significantly decreased, and T, natural killer (NK), CD4+ and CD8+ were not significantly abnormal. The absolute numbers of Th2 cells were lower than healthy group(p=0.043). In particular, the absolute numbers of Treg cells were significantly lower than healthy group(p<0.001), while the absolute numbers of Th17 cells increased(p=0.682). Th17/Treg was significantly higher than healthy group (p< 0.001). Cytokine analysis showed that the level of interleukin (IL)-4 in IRPF patients was higher than healthy group(p=0.011), IL-6, IL-10, IL-17, TNF-α and IFN-γ were significantly higher than healthy group (all p<0.001). Receiver operating characteristic (ROC) curves showed that IL-10 and TNF-α could distinguish bilateral ureteral dilatation in IRPF patients, with areas under the ROC curve (AUCs) of 0.813 (95% CI:0.607-1.000, p=0.026) and 0.950 (95% CI:0.856-1.000, p=0.001), respectively. IL-6 could distinguish bilateral ureteral obstruction, with an AUC of 0.861 (95% CI: 0.682-1.000, p=0.015). Conclusions Our study showed that IRPF patients had reduced Treg cells and indeed had Th17/Treg imbalance, which may be related to the pathogenesis of the disease. The levels of IL-6, IL-10 and TNF-α appear to be associated with the progression of IRPF.